Effect of CD4+ T cell count on treatment-emergent adverse events among patients with and without HIV receiving immunotherapy for advanced cancer. Issue 9 (2nd September 2022) - Odeny, Thomas A; Lurain, Kathryn; Strauss, Julius; Fling, Steven P; Sharon, Elad; Wright, Anna; Martinez-Picado, Javier; Moran, Teresa; Gulley, James L; Gonzalez-Cao, Maria; Uldrick, Thomas S; Yarchoan, Robert; et al.
Abstract : Background: The Food and Drug Administration recommends that people living with HIV (PWH) with a CD4+ T cell count (CD4) ≥350 cells/µL may be eligible for any cancer clinical trial, but there is reluctance to enter patients with lower CD4 counts into cancer studies, including immune checkpoint inhibitor (ICI) studies. Patients with relapsed or refractory cancers may have low CD4 due to prior cancer therapies, irrespective of HIV status. It is unclear how baseline CD4 prior to ICI impacts the proportion of treatment-emergent adverse events (TEAE) and whether it differs by HIV status in ICI treated patients. Methods: We conducted a pilot retrospective cohort study of participants eligible for ICI for advanced cancers from three phase 1/2 trials in the USA and Spain. We determined whether baseline CD4 counts differed by HIV status and whether the effect of CD4 counts on incidence of TEAE was modified by HIV status using a multivariable logistic regression model. Results: Of 122 participants, 66 (54%) were PWH who received either pembrolizumab or durvalumab and 56 (46%) were HIV-negative who received bintrafusp alfa. Median CD4 at baseline was 320 cells/µL (IQR 210–495) among PWH and 356 cells/µL (IQR 260–470) among HIV-negative participants (p=0.5). Grade 3 or worse TEAE were recorded among 7/66 (11%) PWH compared with 7/56 (13%) among HIV-negative participants. When adjusted for prior therapies, age, sex, and race, the effect of baseline CD4 on incidence of TEAE was not modified by HIV status for any TEAE (interaction term p=0.7), or any grade ≥3 TEAE (interaction term p=0.1). Conclusions: There was no significant difference in baseline CD4 or the proportions of any TEAE and grade ≥3 TEAE by HIV status. CD4 count thresholds for cancer clinical trials should be carefully reviewed to avoid unnecessarily excluding patients with HIV and cancer.